tim x 5^3.5^x-2+5^x=150
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4.5\right)=3.5\)
\(=>2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4.5-3.5=0\)
\(=>-6x-8=0\)
\(=>-2\left(3x+4\right)=0\)
\(=>3x+4=0\)(vì \(-2\ne0\))
\(=>x=\frac{-4}{3}\)
Đặt A = \(\frac{1}{3.5}+\frac{1}{5.7}+\frac{1}{7.9}+...+\frac{1}{\left(2x+1\right)\left(2x+3\right)}=\frac{5}{31}\)
2A = \(\frac{2}{3.5}+\frac{2}{5.7}+\frac{2}{7.9}+...+\frac{2}{\left(2x+1\right)\left(2x+3\right)}=\frac{10}{31}\)
2A = \(\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+...+\frac{1}{\left(2x+1\right)}-\frac{1}{2x+3}=\frac{10}{31}\)
2A = \(\frac{1}{3}-\frac{1}{2x+3}=\frac{10}{31}\)
Ta có : \(\frac{1}{3}-\frac{1}{2x+3}=\frac{10}{31}\)
\(\frac{1}{2x+3}=\frac{1}{3}-\frac{10}{31}\)
\(\frac{1}{2x+3}=\frac{1}{93}\)
=> 2x + 3 = 93
2x = 90
x = 45
a,5x+5x+1= 150
\(\Rightarrow5^x.(1+5)=150\)
\(\Rightarrow5^x.6=150\)
\(\Rightarrow5^x=150:6\)
\(\Rightarrow5^x=25\)
\(\Rightarrow5^x=5^2\)
\(\Rightarrow x=2\)
\(5^x=125\)
\(5^x=5^3\)
=> x=3 ( vì cơ số 5>1)
\(3^2.x=81\)
\(9x=81\)
\(x=81:9\)
\(x=9\)
\(\frac{1}{1.3}+\frac{1}{3.5}+\frac{1}{5.7}+...+\frac{1}{x.\left(x+2\right)}=\frac{5}{11}\)
\(\Rightarrow\frac{1}{2}\left(1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{x}-\frac{1}{x+2}\right)=\frac{5}{11}\)
\(\Rightarrow\frac{1}{2}\left(1-\frac{1}{x+2}\right)=\frac{5}{11}\Rightarrow1-\frac{1}{x+2}=\frac{5}{11}\div\frac{1}{2}=\frac{10}{11}\)
\(\Rightarrow\frac{1}{x+2}=1-\frac{10}{11}=\frac{1}{11}\Rightarrow x+2=11\Rightarrow x=11-2=9\)
\(\frac{1}{1.3}+\frac{1}{3.5}+......+\frac{1}{x+\left(x+2\right)}\)
\(=1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+........+\frac{1}{x}-\frac{1}{x+2}\)
\(=1-\frac{1}{x+2}=\frac{5}{11}\)
\(\frac{1}{x+2}=1-\frac{5}{11}=\frac{6}{11}\)
=> không có kết quả
\(\Rightarrow5\left(x-10\right)=2\left(x+2\right)\)
\(\Rightarrow5x-50=2x+4\)
\(\Rightarrow3x=54\Rightarrow x=18\)
5x - 50 = 2x + 4
=> 5x - 50 - 2x - 4 = 0
x( 5 - 2 ) - ( 50 + 4 ) = 0
3x - 54 = 0
3x = 54
x = 18